Wulgarny internauta, czyli kilka słów o zgorszeniu w sieci - Kuruc, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Vulgar surfer or a few words about the network profanity There has been a common belief that an Internet language is full of vulgarism. The level of interpersonal culture in communication has been lowering, especially in functional aspect of language. Moreover, vulgarization of speech is getting forward, which is being noticed in many different communicational situations in the global network. In the Internet, vulgarisms usually appear in different than traditional meanings and they also play different functions. They can be written with the use of symbols available on a keyboard, euphemism or graphical elements. Acronyms and emoticons are also elements of language that are part of the web communication. It is also noticeable that the range of occurrence of vulgar words is getting wider and the feeling of vulgarity is getting weaker and weaker. In certain circles of users there can be seen even desemantization of vulgarisms that are used as interlude or substitute for many more semantically rich precise words. There has been popularization of colloquial elements leading to neutralization of expressivisms and replacing them with vulgarisms that are used to express mostly negative, angry and aggressive feelings. The analysis of the forms mentioned above underlines present deliberation.